Lecturers and Students’ Perception on Politeness in Communication: Definition and Importance - Anugrawati, Nunung; Syam, Ummi Khaerati; Muhsin, Muh. Arief (Universitas Cokroaminoto Palopo, 2024)
This research aimed at exploring lecturers and students’ perception on politeness in academic setting. This research employed a descriptive qualitative research. The participants of this research were seven lecturers of English Department, Muhammadiyah University of Makassar, selected based on some criteria, and the students of those lecturers. The data were collected through interview and focus group discussion. The data obtained from the instruments were transcribed and then analyzed qualitatively to meet the interpretation. The data gained through interview stated that lecturers and students perceived politeness as academism or formality and expression of emotional bonding. The meaning of academism or formality is talking using standard or acceptable language based on the shared culture and context of language usage. In addition, lecturer believes that politeness is an essential expression of feeling among humans showing an emotional bonding. When people have good relationships with others, they tend to consider politeness in communicating one another. Lecturers and students also viewed that politeness was very important in academic context, since it was a part of character education building and culture representation.